2016
DOI: 10.1111/pme.12893
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Recurrence and Regional Anesthesia: The Theories, the Data, and the Future in Outcomes

Abstract: Objective. More than one million people each year in the United States are diagnosed with cancer. Surgery is considered curative, but the perioperative phase represents a vulnerable period for residual disease to spread. Regional anesthesia has been proposed to reduce the incidence of recurrence by attenuating the sympathetic nervous system's response during surgery, reducing opioid requirements thus diminishing their immunosuppressant effects, and providing antitumor and antiinflammatory effects directly thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 111 publications
(104 reference statements)
0
40
0
5
Order By: Relevance
“…μ‐opioid receptor overexpression, which may influence tumor growth and cancer progression, was noted in several cancers including non‐small cell lung, prostate, and breast. However, studies of high morphine doses in mice do not demonstrated tumor progression . Opioids were shown to stimulate angiogenesis in some but not all studies of human endothelial cells and mice .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…μ‐opioid receptor overexpression, which may influence tumor growth and cancer progression, was noted in several cancers including non‐small cell lung, prostate, and breast. However, studies of high morphine doses in mice do not demonstrated tumor progression . Opioids were shown to stimulate angiogenesis in some but not all studies of human endothelial cells and mice .…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this, opioids enhance apoptosis in breast cancer, small cell lung cancer, and prostate cancer cells, suggesting opioids may have anticancer effects . Finally, opioids may suppress immune function, in particular natural killer cells, which spontaneously recognize and kill a variety of tumor cells . Opioids may also increase concentrations of vascular endothelial growth factor, which increases angiogenesis and cell migration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recently published study [8], investigators reported that for many patients taking opioids before joint replacement surgery, as well as some opioid-naïve patients undergoing arthroplasty procedures, opioid use persisted after surgery despite the absence of joint pain. Retrospective studies have also found an association between the use of large doses of opioid analgesic medication during the perioperative period in patients undergoing primary tumor resections and the recurrence of cancer within 5 years [9].…”
Section: Introductionmentioning
confidence: 99%